Keanekaragaman beserta karakteristik habitat Famili Panorpidae (Ordo: Mecoptera) di Taman Hutan Raya Ir. H. Djuanda Bandung: Diversity and habitat characteristic of Panorpidae family (Order: Mecoptera) in Taman Hutan Raya Ir. H. Djuanda Bandung - Ardyanty, Putry; Widiana, Ana; Kinasih, Ida (Jurnal Entomologi Indonesia, 2023)
Mecoptera is a primitive and minor order of insects with nine families, including Panorpidae. Research on Panorpidae in Indonesia is lacking, especially regarding its habitat. Thus, the purpose of this study was to observe the diversity and habitat characteristics of Panorpidae. The study was conducted at Taman Hutan Raya Ir. H. Djuanda Bandung from March to April 2023. The survey method was conducted at plots in three area blocks: the utilization block, the protection block, and the collection block. Panorpidae were collected by hand and sweeping net and then identified based on morphological characteristics. Temperature, humidity, light intensity, and vegetation where Mecoptera are found are identified and recorded. This study collected one genus (Neopanorpa) and five species found in the protection block (there were five species) and the utilization block (there were three species) while none in the collection block. The Penorpidae population was higher at the Protection block than at the Utilization block. Generally, Panorpidae was found in broad-leaf vegetation such as Clidemia sp. and Datura sp., with a canopy that is not too dense. The level of diversity and evenness of both areas was medium. Humidity positively affects the diversity and abundance of Panorpidae, while temperature and light intensity have negative effects. This research shows that Panorpidae likes damp places protected by bush vegetation and under not too dense canopy.